2006
DOI: 10.1097/01.jom.0000183539.20100.06
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin Lymphoma, Multiple Myeloma, Soft Tissue Sarcomas, Insect Repellents, and Phenoxyherbicides

Abstract: The mechanisms by which phenoxyherbicides contribute to the risk of multiple myeloma and non-Hodgkin lymphoma may be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…27 No additional risk of developing STS, MM, and HL were observed from this combination of exposures (DEET, mecoprop, and the use of rubber gloves). 23 The combinations of exposure to pesticide ≥10 hours per year and positive family history of cancer increased the risk of NHL and MM. 22 In a recent publication of STS and pesticides exposure reported that insecticides aldrin and diazinon were significantly associated with increased risk of STS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…27 No additional risk of developing STS, MM, and HL were observed from this combination of exposures (DEET, mecoprop, and the use of rubber gloves). 23 The combinations of exposure to pesticide ≥10 hours per year and positive family history of cancer increased the risk of NHL and MM. 22 In a recent publication of STS and pesticides exposure reported that insecticides aldrin and diazinon were significantly associated with increased risk of STS.…”
Section: Discussionmentioning
confidence: 99%
“…The study also had limitations common in casecontrol studies, which have been discussed in other publications. [22][23][24] This study had potential for recall bias and for misclassification of pesticides exposure and duration of exposure. This study did not have large enough numbers to evaluate dose-response relationships between specific pesticides and HL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Besides being at risk for injury, farmers are also at risk for developing cancers and neurodegenerative or respiratory disorders as a result of occupational hazards. 5,6 Other reported health hazards and impairments include hearing loss, 7 arthritis, 8 and skin diseases. 9,10 Increased incidence of mental stress and mental illness among farmers has been documented.…”
Section: Introduction Backgroundmentioning
confidence: 99%